2011
DOI: 10.2119/molmed.2011.00210
|View full text |Cite
|
Sign up to set email alerts
|

Local Fetal Lung Renin-Angiotensin System as a Target to Treat Congenital Diaphragmatic Hernia

Abstract: Antenatal stimulation of lung growth is a reasonable approach to treat congenital diaphragmatic hernia (CDH), a disease characterized by pulmonary hypoplasia and hypertension. Several evidences from the literature demonstrated a possible involvement of renin-angiotensin system (RAS) during fetal lung development. Thus, the expression pattern of renin, angiotensin-converting enzyme, angiotensinogen, type 1 (AT 1 ) and type 2 (AT 2 ) receptors of angiotensin II (ANGII) was assessed by immunohistochemistry throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 62 publications
1
30
2
Order By: Relevance
“…Many factors that regulate fetal lung branching morphogenesis activate signaling pathways that culminate with MAPK, PI3K/Akt and p38 cascades [30,31,40,41,42]. In the present study, ephrin-B1 was found not to modify the phosphorylated levels of these proteins.…”
Section: Discussioncontrasting
confidence: 53%
“…Many factors that regulate fetal lung branching morphogenesis activate signaling pathways that culminate with MAPK, PI3K/Akt and p38 cascades [30,31,40,41,42]. In the present study, ephrin-B1 was found not to modify the phosphorylated levels of these proteins.…”
Section: Discussioncontrasting
confidence: 53%
“…According to the nitrofen‐induced CDH rat model, randomly selected pregnant rats received 100 mg of nitrofen (2,4‐dichlorophenyl‐ p ‐nitrophenylether) dissolved in 1 ml of olive oil via gavage on 9.5 dpc (days postconception) (hypoplastic group) (Nogueira‐Silva et al . ). Control animals only received only olive oil (control group).…”
Section: Methodsmentioning
confidence: 97%
“…; Nogueira‐Silva et al . ). This congenital anomaly is characterised by a diaphragmatic defect that allows intra‐thoracic herniation of abdominal organs and maldevelopment of the alveoli and pulmonary vessels (van Loenhout et al .…”
Section: Introductionmentioning
confidence: 97%
“…The majority of preclinical studies have focused on vitamin or steroid administration [8,9]. Isolated studies on transplacental therapies in the nitrofen rat model have been published, including sildenafil (VEGF agonist), CGS-26303 (endothelin-converting enzyme-1 activator), PR-123319 (angiotensin 2 receptor antagonist), epidermal growth factor, ghrelin, estrogen, and tetrandrine (a Chinese herbal remedy) [10,11,12,13,14,15,16]. Only tadalafil has been used transplacentally in the sheep model [17].…”
Section: Introductionmentioning
confidence: 99%